Аналіз ефективності регулювання системи аварійного охолоджування активної зони насосами високого тиску на АЕС з ВВЕР-1000/В320 - Skalozubov, V.; Komarov, Yu.; Bogodist, V.; Vorobiev, Yu.; Foltov, I. (State Scientific and Technical Center for Nuclear and Radiation Safety, 2010)
Installation of stop-check valves for HPSIS at WWER-1000/V-320 can be effective only if there are additional adjustments to incorporate the velocity of the stop-check valve plunger and the configuration of systems that provide cooling of the primary circulation loop.